Villages in the city : a guide to South China's informal settlements - Al, Stefan (Hong Kong University Press, 2014)
Urban villages are a unique phenomenon that shows an interesting side of urban and demographic change in China. This book argues for the value of urban villages as places. To reveal their qualities, a series of drawings and photographs uncovers the immense concentration of social life in their dense structures and provides a peek into residents' homes and daily lives. Organized in a guidebook fashion and lavishly illustrated, the book embodies a different type of scholarly work that is accessible to general readers. Essays written from the disciplines of urban planning, geography and architect.